Role of Intestinal Transit in the Pathogenesis of Gallbladder Stones - R Hermon Dowling; Martin J Veysey; Stephen P Pereira; S Hyder Hussaini; Linzi A Thomas; John AH Wass; Gerard M Murphy (Canadian Journal of Gastroenterology)
Increasing evidence implicates prolonged intestinal transit (slow transit constipation) in the pathogenesis of conventional gallbladder stones (GBS), and that of gallstones induced by long term octreotide (OT) treatment. Both groups of GBS patients have multiple abnormalities in the lipid composition and physical chemistry of their gallbladder bile - associated with, and possibly due to, an increased proportion of deoxycholic acid (DCA) (percentage of total bile acids). In turn, this increase in the percentage of DCA seems to be a consequence of prolonged colonic transit. Thus, in acromegalic patients OT treatment significantly prolongs large bowel transit time (LBTT) and leads to an associated increase of the percentage of DCA in fasting serum (and, by implication, in gallbladder bile). LBTT is linearly related to the percentage of DCA in fasting serum and correlates significantly with DCA input (into the enterohepatic circulation) and DCA pool size. However, these adverse effects of OT can be overcome by the concomitant use of the prokinetic drug cisapride, which normalizes LBTT and prevents the rise in the percentage of serum DCA. Therefore, in OT-treated patients and other groups at high risk of developing stones, it may be possible to prevent GBS formation with the use of intestinal prokinetic drugs.